Detraining’s Effects on Cardiorespiratory Fitness and Maximal and Explosive Strength in Army Soldiers: Does Age Matter? - Alexis Arce-Álvarez; Ángelo Zaio; Camila Salazar-Ardiles; Cristian Álvarez; Pablo Merino-Muñoz; Manuel Vasquez-Muñoz; Mikel Izquierdo; Mauricio Castro; David C. Andrade (Sports, 2024)
Purpose: This study investigated the impact of four weeks of age-dependent detraining on army soldiers’ cardiorespiratory fitness and maximal and explosive strength. Methods: Fourteen volunteer tactical athletes participated, divided into two age groups (20 to 29 and 30 to 40 years). Before and after the detraining period, we assessed their anthropometric measurements (weight, height, body mass index, fat mass, and fat-free mass), cardiorespiratory fitness (maximal oxygen uptake [VO2max] and ventilatory thresholds [VT1 and VT2]), and kinematic properties during a single-leg counter-moving jump (CMJ) test for both the dominant and non-dominant legs. Two-way ANOVA followed by the Holm–Sidak post hoc test was used. Results: The anthropometric and cardiovascular variables did not show significant differences between the groups. However, both groups exhibited a significantly reduced maximum time and speed at the VO2max. Furthermore, the flight time and maximum height during the CMJ significantly decreased in the non-dominant leg for both age groups. Notably, the dominant leg’s concentric impulse (CI) significantly reduced during the CMJ, but this effect was observed only in the 30–40 age group. There were significant differences between the two age groups. Conclusions: Our findings suggest that four weeks of detraining negatively impacts aerobic fitness and muscular strength, independently of age. However, the dominant leg may be more susceptible to detraining effects in army soldiers aged 30–40. Furthermore, as a perspective, our results strongly suggest that a detraining period could affect successful missions (aerobic performance deterioration), as well as promote a muscle imbalance between the legs, which could encourage muscle injuries and endanger combat missions.